ripley's publishing rbi fact or fiction? bureau of investigation: sub-zero survival - Publishing Ripley's; Ripley's Publishing (United States Ripley's Publishing, 2010)
Ripley's Bureau of Investigation (RBI) 6: Sub-Zero Survival is a children's fiction action-adventure book published by Ripley Publishing, targeting readers aged 7 to 12. While it is part of the "Ripley's Believe It or Not!" brand$1 (Bwhich is renowned for gathering true, unusual facts$1 (Bthis book series follows a fictional team of teen agents with special gifts. s
English